Civic Value dalam Pendidikan Multikultural:Upaya Membangun Toleransi dan Kohesi Sosial Siswa - Indarwati, Indarwati; Mahardhani , Ardhana Januar; Cahyono, Hadi (JPK (Jurnal Pancasila dan Kewarganegaraan), 2025)
This research seeks to examine how incorporating civic values into multicultural education can promote tolerance and enhance social unity among students at SMPN 4 Ponorogo. Employing a descriptive qualitative method, data were gathered via in-depth interviews, participatory observations, and document analyses concerning civics educational practices and school policies that promote citizenship values. The results indicate that the integration of civic values is achieved through three key strategies: (1) the incorporation of citizenship values in teaching that highlights respect for diversity, equal communication, and conflict resolution; (2) the enhancement of an inclusive school environment via collaborative activities among diverse backgrounds that foster empathy and social consciousness; and (3) the establishment of positive social interactions that cultivate solidarity and enhance relationship networks among students. These approaches effectively cultivate accepting mindsets, collaborative abilities, and receptiveness to diversity as vital components of democratic citizenship. The incorporation of multicultural education and civic values greatly enhances the development of a harmonious, democratic, and socially united school atmosphere. The research suggests reinforcing dialogic learning initiatives, improving intercultural partnerships, and creating more structured school policies to guarantee the ongoing internalization of citizenship values.